An ambiguous partnership of word and tone: media “confrontation” in Mozart’s Don Giovanni - Martina Viljoen (Acta Academica, 2006)
Mozart’s opera Don Giovanni is generally recognised as the greatest work dealing with the theme of Don Juan. It is also extremely complex and raises in an unusually challenging way the significance of the figure of Don Giovanni. This article examines the relevance of Nicholas Cook’s theory regarding the analysis of musical multimedia. Focusing also on the works of Wye Jamison Allanbrook and Leonard Ratner that have a bearing on the topic, it explores Mozart’s ingenious deployment of musical expression, style, and syntax in the opera as primary agents in the construction of human character. Cook’s “contest” model postulates that the projection of Don Giovanni’s character owes its complexity to a remarkably ambiguous partnership of word and tone, resulting in what may be called a “contradiction” of musical and verbal meaning.